EFFICIENCY OF BIOLOGICAL TREATMENT FOR THE REMOVAL OF TOTAL AND THERMOTOLERANT COLIFORM BACTERIA FROM DOMESTIC SEWAGE - Pilotto Branco, Paula Maria [UNESP]; Sandoval Nogueira, Ricardo Galbiatti; Soares Ferreira, Livia Maria [UNESP]; Amaral, Luiz Augusto do [UNESP]; Lucas Junior, Jorge de [UNESP] (Univ Federal Uberlandia, 2016)
Researchers around the world have focused their efforts on devising combinations of technologies that are not only economically feasible but also effective in mitigating the impacts caused by wastes containing pathogens that pose potential risks to human and animal health. The purpose of this study was to evaluate the performance of a biological treatment system for removing total and thermotolerant coliform bacteria with a view to the possible organic recycling of domestic sewage. To this end, a tubular continuous flow anaerobic digester, with hydraulic retention time (HRT) of 25 days and an optional stabilization pond, were used to treat the sewage produced by 150 people in the municipality of Sertaozinho, SP, Brazil. The samples were collected weekly, always on the same day, at three different sampling points (inlet of the treatment system, the outlet of tubular digester, and the optional stabilization pond), totaling 108 samples. The MPN method was employed to determine the total coliform and thermotolerant coliform populations, using multiple series of three tubes (APHA, 2005). The system proved efficient in reducing the number of indicator bacteria of fecal contamination, showing a removal efficiency of 98.76% for total coliforms and of 99.29% for thermotolerant coliforms. However, a third treatment step involving polishing should be included to render the effluent suitable for use in fertigation or discharge into water bodies.
Keywords: Continuous flow anaerobic digester; Environmental sustainability; Indicator bacteria; Sewage; Stabilization pond